THE PRACTICE OF USING DESIGN-THINKING TECHNIQUES IN THE “ONLINE ENTREPRENEURSHIP” TRAINING COURSE: FROM AN IDEA TO PROTOTYPING - N. F. Altukhova; E. V. Vasilieva (Финансы: теория и практика)
The paper examines the experience of applying new experimental education methods to the development of creative abilities, research skills and building communications in the staff training for technological entrepreneurship. Not long ago, universities began to include the technological business course into the educational process. To learn how to code, promote one’s project over the Internet using well-known online marketing technologies, project management methodologies, management principles, techniques of interviewing potential users to determine the usefulness of a non-existent but almost created and almost sold product is not difficult. But it is one thing to speak about the already established methods of analyzing the success of the promotion of a product, a website, an advertising message on the Internet that can be tested on ready solutions, and quite the other thing is to teach a person to conceive an idea, analyze its feasibility, evaluate its competitive advantages, create a prototype and launch it into the test environment. The authors propose to consider the design thinking techniques precisely in the context of their applicability at the initial stages of a startup company’s life cycle. The key stages of the design thinking process - empathy, focusing, generation, selection, prototyping and testing - are built on the ability to quickly generate a variety of ideas that make it possible to get away from banality as well as on rules of choosing the best solution, its embodiment, even at the prototype level, and testing. The sessions are based on game mechanics and cases that allow development of solutions for abnormal situations.